Therapy with mTOR Inhibitors in Polyomavirus Allograft Nephropathy (PVAN): A Five Year Follow Up - Ana Theresa Guanaes Bonini; André Barros Albuquerque Esteves; Leonardo Figueiredo Camargo; Carla Feitosa do Valle; Gabriel Giollo Rivelli; Marcos Vinícius de Sousa; Marilda Mazzali (Archives of Organ Transplantation - Peertechz Publications, 2017)
Polyomavirus nephropathy (PVAN) has a negative impact on renal allograft survival. Therapy options include reduction of immunosuppression and antiviral drugs. Aim: Evaluate the effect ofmTORi based immunosuppression on PVAN.  Methods: Cross-sectional cohort of 21 renaltransplant recipients with PVAN. Initial immunosuppression based on MPA/tacrolimus was changed to mTOR/steroids at diagnosis, if urine protein/creatinine ratio <0.5 g/l. Patients weremonitored by urine cytology, qualitative PCR in peripheral blood, serum creatinine andprotein/creatinine ratio. Results: PVAN was suspected 14.3±19.3 months post-transplant, by thepresence of decoy cells in serial urine cytology. At this point, serum creatinine was 1.4 ± 0.5 mg /dL, through levels of tacrolimus (TAC) was 8.6 ± 3.5 ng/dL. TAC dose was reduced (through level 6.8 ± 2.8 ng/dL). However, in presence of persistent viruria and allograft dysfunction (creatinine 2.5 ± 0.7 mg/dL), a biopsy was performed 30.0±18.1 months post-transplant, with the final diagnosis of PVAN stage 2. MPA and TAC were withdrawn and immunosuppressive therapy maintained with mTORi (sirolimus or everolimus) plus steroids. No rejection episodes were observed. In a 5-year follow up, 10/21 (47.6%) grafts were lost due progression of PVAN. Risk factors for graft loss were higher creatinine at first viruria (1.7 ± 0.7 versus 1.4 ± 0.4 mg/dl, p<0.05) or at biopsy (3.1 ± 0.6 versus 2.3 ± 0.7 mg / dl), compared to group with a functioning graft after 5 years. In the latter group, after 70 months of follow-up, renal function remained stable (creatinine 2.0 ± 0.5 mg/dl); with negative viruria 16 weeks post mTORi. Conclusion: In this series, the change of immunosuppression to mTORi and prednisone was safe with cleared viruria onaverage 16 weeks after conversion. In patients with earlier renal biopsy and with better renal function, this strategy preserved the allograft function.